2012
DOI: 10.1002/jcu.21989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retrobulbar blood flow by color doppler ultrasonography after intravitreal ranibizumab injection in patients with neovascular age‐related macular degeneration

Abstract: Intravitreal ranibizumab injection for neovascular AMD does not cause a significant change in the retrobulbar blood flow in either the injected eye or the fellow eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is worth noting the possible influence of anti-VEGF treatment on TRBF in the eyes with DME because anti-VEGF agents have been linked to transient reductions in RBF . For the 6 eyes that received anti-VEGF treatment, the injections were given based on a treat-and-extend protocol.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting the possible influence of anti-VEGF treatment on TRBF in the eyes with DME because anti-VEGF agents have been linked to transient reductions in RBF . For the 6 eyes that received anti-VEGF treatment, the injections were given based on a treat-and-extend protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the PSV and EDV are, the more sufficient the blood supply is (20). RI and PI reflect the blood flow resistance of blood vessels and are negatively related to vascular compliance (21). The results demonstrated that anti-VEGF drugs, combined with PDT, can optimize blood flow state, which is the fundamental mechanism behind vision changes in patients.…”
Section: Discussionmentioning
confidence: 99%